2021
DOI: 10.3390/polym13132084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of a Novel Glycidyl Metharcylate/Phaytic Acid-Based on Bagasse Xylan Composite Derivative

Abstract: The development of natural biomass materials with excellent properties is an attractive way to improve the application range of natural polysaccharides. Bagasse Xylan (BX) is a natural polysaccharide with various biological activities, such as antitumor, antioxidant, etc. Its physic-chemical and biological properties can be improved by functionalization. For this purpose, a novel glycidyl metharcylate/phytic acid based on a BX composite derivative was synthesized by a free radical polymerization technique with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In a previous study, Res was shown to act synergistically with dihydroartemisinin (DHA) in HepG2 and MDA-MB-231 cancer cells, and the combination controlled the migration of cancer cells with a stronger inhibitory effect than with Res and DHA alone [ 27 ]. This suggests that when multiple substances with antitumor activity are used in combination, the effect may be even stronger [ 28 , 29 , 30 ], which suggests the potential value of studying the synergistic effects of various compounds and their composite modification.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Res was shown to act synergistically with dihydroartemisinin (DHA) in HepG2 and MDA-MB-231 cancer cells, and the combination controlled the migration of cancer cells with a stronger inhibitory effect than with Res and DHA alone [ 27 ]. This suggests that when multiple substances with antitumor activity are used in combination, the effect may be even stronger [ 28 , 29 , 30 ], which suggests the potential value of studying the synergistic effects of various compounds and their composite modification.…”
Section: Introductionmentioning
confidence: 99%